Conocimiento y actitud hacia el procedimiento mamá canguro en el personal de enfermería del servicio de neonatología Hospital Regional de Loreto Iquitos 2024 - Díaz Sangama, Adita Adbeel (2025)
The objective was to determine the relationship between knowledge and attitude toward the kangaroo mother care procedure in the nursing staff of the Neonatology Service at the Regional Hospital of Loreto, Iquitos 2024. The approach was quantitative, and the design used was non-experimental, descriptive, cross-sectional, and correlational. The population and sample consisted of 64 nursing staff from the Neonatology Service of the Regional Hospital of Loreto. The technique was survey and interview; the instruments were the Questionnaire on Knowledge about the Kangaroo Mother Care Procedure and the Likert-Type Scale on Attitude Toward the Kangaroo Mother Care Procedure. SPSS version 27.0 statistical software was used to analyze the data, and correlations were examined using Kendall's Tau-b statistical test with a significance level of 95% and alpha (p < 0.05). According to the results, regarding knowledge about the kangaroo mother care procedure, 68.8% showed low levels of knowledge, 29.7% showed medium levels of knowledge, and the remaining 1.6% showed high levels of knowledge. Regarding attitudes toward the kangaroo mother care procedure, 70.35% showed rejection, 25.0% showed indifference, and the remaining 4.7% showed acceptance. In conclusion, a strong positive relationship was demonstrated between knowledge and attitudes toward the kangaroo mother care procedure, as measured by Kendall's Tau-b coefficient of 0.000 (p < 0.05).